2001
DOI: 10.1128/jb.183.20.5855-5861.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Contribution of Point Mutations tovlsEVariation and for Apparent Constraints on the Net Accumulation of Sequence Changes invlsEduring Infection with Lyme Disease Spirochetes

Abstract: In the Lyme disease spirochetes, both the ospE and vlsE gene families have been demonstrated to undergo sequence variation during infection. To further investigate the mechanisms associated with the generation of vls variation, single-nucleotide polymorphism and subsequent DNA sequence analyses were performed on the vlsE gene and its paralog, BBJ51, a related gene with a frameshift mutation. These analyses focused on a series of postinfection clonal populations obtained from mice infected with Borrelia burgdor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
(29 reference statements)
2
30
2
Order By: Relevance
“…vlsE gene expression is increased following exposure of B. burgdorferi to endothelial cell membranes or intact endothelial cells in vitro (29), indicating that VlsE may fall into a growing class of genes that are up-regulated in the mammalian environment. Furthermore, vlsE recombination occurs at a rapid rate during infection of either immunocompetent or immunodeficient mice but has not been detected during in vitro culture (7,30). It was reported by Ohnishi and de Silva (31) that B. burgdorferi in ticks inoculated by feeding on infected mice contained vlsE sequence variants that either arose within the ticks or were selected during the second feeding.…”
Section: Resultsmentioning
confidence: 99%
“…vlsE gene expression is increased following exposure of B. burgdorferi to endothelial cell membranes or intact endothelial cells in vitro (29), indicating that VlsE may fall into a growing class of genes that are up-regulated in the mammalian environment. Furthermore, vlsE recombination occurs at a rapid rate during infection of either immunocompetent or immunodeficient mice but has not been detected during in vitro culture (7,30). It was reported by Ohnishi and de Silva (31) that B. burgdorferi in ticks inoculated by feeding on infected mice contained vlsE sequence variants that either arose within the ticks or were selected during the second feeding.…”
Section: Resultsmentioning
confidence: 99%
“…It is evident from the chronic nature of Lyme disease that the Lyme disease spirochetes are able to evade immune destruction. Several potential mechanisms of immune evasion have been identified (22,23,33,34,36,37). It has recently been demonstrated that some Borrelia species can bind the complement regulatory proteins factor H and or factor H like-protein 1 (FHL-1) to their surface (2,18,24,29).…”
mentioning
confidence: 99%
“…Borrelia Outer surface protein C (OspC) [3] and Vmplike sequence expressed (VlsE) [4] are two plasmid encoded membrane proteins that both are immunodominant antigens. Furthermore, VlsE consists of one invariable region (IR6), which is extraordinary immunodominant [5,6].…”
mentioning
confidence: 99%